Latex–collagen membrane: an alternative treatment for tibial bone defects - de Paiva, Marcela Britto; Pegorin Brasil, Giovana Sant’Ana [UNESP]; Chagas, Ana Laura Destro [UNESP]; Macedo, Ana Paula; Ramos, Júnia; Issa, João Paulo Mardegan; Gangrade, Ankit; Floriano, Juliana Ferreira [UNESP]; Caetano, Guilherme Ferreira; Li, Bingbing; Farhadi, Neda; Mandal, Kalpana; et al. (My University, 2022)
Due to the difficulty of consolidation, the risk of fractures, and the high cost of therapy, the orthopedic field views the restoration of bony defects or post-traumatic diseases as a significant issue. In recent years, efforts have been made toward guided bone regeneration as a viable solution. In this study, natural rubber latex (NRL) and latex–collagen (NRL-COL) membranes were developed and characterized, and their effects on bone regeneration in rat tibial lesions were assessed. According to the physicochemical findings, the hydrolyzed COL was effectively incorporated into the NRL membrane to produce a more robust membrane (348% increase in stress) and showed good biocompatibility for human dermal fibroblast cells and in hemolytic activity assay. According to bone analysis using computed microtomography, a substantial difference in bone volume (BV) was found among NRL, control (CONT), and NRL-COL. NRL-COL exhibited the greatest value for the bone volume/total volume ratio (BV/TV). The presence of NRL and COL was significant for the analysis of BV and BV/TV, respectively. All the experimental groups demonstrated a higher bone quality and fracture resistance, as shown by the mechanical properties of the bone. In the COL group, both neoformation of bone and total collagen levels were greater, indicating that treated defects had been closed and mature bone cells were present. Due to its angiogenic properties and the low cost of NRL membrane production, the NRL-COL membrane could be a good substitute for upcoming bone regeneration applications. Graphical Abstract: [Figure not available: see fulltext.]